ENGINEERING WEB-BASED INFORMATION SYSTEMS FOR MANAGEMENT OF WOMEN AND CHILD PROBLEM HANDLING ACTIVITIES - Zaidir Zaidir; Indra Listiawan (Compiler, 2020)
The problem of violence against women and children, viewed from an individual as well as a social perspective, can have multiple effects. The effects such as psychological and individual health and the quality of public health. Women and children in everyday life often receive unpleasant treatment from close people and strangers. The constraints experienced are that often the two affairs are combined and handled by one sector, the number of officers is less than the cases handled, there is not enough budget to carry out follow-up actions and many residents do not want to disclose their problems directly to the authorities. There are many problems for women and children, so a "Task Force for Handling Women and Children Problems (Satgas PPA)", both at the central and regional levels. The activities of the PPA Task Force include: outreach, identification of conditions and services needed, protection of women and children at the scene (emergency assistance), placement and displacement of women and children who experience problems and referrals and / or recommendations. The research objective was to produce a management system for handling women and children activities in the village of Katekan, Gantiwarno, Klaten. The research method used consists of literature study, data collection and system development with the Waterfall method. The result of this research is a system capable of managing the activities of the task force handling women and children that can provide information in all variations to help make decisions. This system is built using PHP programming and MySQL DBMS.